MicroRNA-653-5p Promotes Gastric Cancer Proliferation and Metastasis by Targeting the SOCS6-STAT3 Pathway - Li, Zengliang; Fan, Hao; Chen, Wangwang; Xiao, Jian; Ma, Xiang; Ni, Peidong; Xu, Zekuan; Yang, Li (Frontiers in Molecular Biosciences, 2021)
MicroRNAs (miRNAs) are emerging as significant regulators of gastric cancer (GC) tumorigenesis, and may be effective biomarkers for diagnosis, prognosis, and therapeutic targeting for GC. In this study, miR-653-5p was found to be significantly upregulated in GC tissues, serum, and cell lines, and was strongly associated with poor prognosis in patients with GC. Furthermore, miR-653-5p promoted GC cell proliferation and metastasis in vivo and in vitro. Suppressor of cytokine signaling 6 (SOCS6) was directly targeted by miR-653-5p, and SOCS6 attenuated miR-653-5p-mediated GC cell growth, migration, and invasion. In addition, SOCS6-mediated inactivation of the Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) signaling pathway was also reversed by administration of miR-653-5p. Our findings support a novel regulatory axis between miR-653-5p, SOCS6, and JAK2/STAT3 that may be a target for diagnosis and therapeutic intervention for GC.